Conditions for Growth and Retreat of the Laurentide Ice Sheet - Budd, William; Smith, Ian (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1987)
ABSTRACTResults of three dimensional numerical modelling of the North American ice sheets in response to the Earth's orbital radiation variations are reviewed in relation to the conditions for formation and retreat of the ice sheets. The last interglacial develops as a clear result of the preceding high summer radiation levels and is not very dependent on the climatic paramaterisation. The magnitude and timing of the last glacial maximum provides a means of fine tuning the climatic parameterisation. In between these two periods the extent of ice sheet advances and retreat is strongly sensitive to the magnitude of the ice sheet albedo feedback parameter. The time changes of the radiation, climate, ice sheet cover and bedrock depression are out of phase and as a result equilibrium is not attained. The distribution of land surface elevation plays a key role in the pattern of seeding of the ice sheet growth and the subsequent advances, coalescence and retreat. The dispersal pattern of bedrock in till can be expected to reflect the growth and advance phases of the ice sheet development rather than the maximum configuration. Finally, the cycles of ice ages over the last 500,000 years from the modelling follows the occurrence of extreme summer radiation levels over a wide latitude band of 40-80°N due to coincidence of obliquity and perihelion features superimposed on the hysteresis effects of the ice cover.